2015
DOI: 10.1371/journal.pone.0140926
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Humoral Immune Responses against HPV16, HPV18, HPV31 and HPV45 in 12-15 Year Old Girls Receiving Cervarix® or Gardasil® Vaccine

Abstract: BackgroundHuman papillomavirus (HPV) vaccines confer protection against the oncogenic genotypes HPV16 and HPV18 through the generation of type-specific neutralizing antibodies raised against virus-like particles (VLP) representing these genotypes. The vaccines also confer a degree of cross-protection against HPV31 and HPV45, which are genetically-related to the vaccine types HPV16 and HPV18, respectively, although the mechanism is less certain. There are a number of humoral immune measures that have been exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…The quadrivalent HPV L1 vaccine has been proven to provide excellent prophylaxis against infection with the 4 HPV types at the primary sites of the cervix and anus, and also some cross‐protection against non‐vaccine types (closely‐related types) 11, 12…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The quadrivalent HPV L1 vaccine has been proven to provide excellent prophylaxis against infection with the 4 HPV types at the primary sites of the cervix and anus, and also some cross‐protection against non‐vaccine types (closely‐related types) 11, 12…”
Section: Discussionmentioning
confidence: 99%
“…The quadrivalent HPV L1 vaccine has been proven to provide excellent prophylaxis against infection with the 4 HPV types at the primary sites of the cervix and anus, and also some cross-protection against non-vaccine types (closely-related types). 11,12 The high production of anti-L1 antibodies induced by the quadrivalent vaccine has been shown to be the primary mechanism of prophylaxis against infection by the 4 main HPV types. It is unclear whether this high protective antibody level is able to yield therapeutic benefits in patients already infected with the virus and with the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Second, VLPs stimulate B-lymphocytes and induce T-lymphocytes in the same manner as does the virus infecting the host organism [30]. For example, VLPs formed by the main capsid protein L1 of the human papilloma virus of several serotypes are successfully used as vaccines against cervical cancer [37]. A vaccine against hepatitis B virus has been produced which contains VLPs in the lipid membrane envelope [38].…”
Section: Natural Sources For Vlp Bioengineering and The Specificmentioning
confidence: 99%
“…The most wellknown are the Cervarix® and Gardasil® vaccines against cervical cancer, which have been successfully used for prophylaxis of this disease in girls for more than ten years. Both vaccines are based on VLPs formed by the main capsid protein L1 of the human papilloma virus belonging to several serotypes [37]. Engerix and Recombivax HB vaccines against the hepatitis B virus representing VLPs enveloped in a lipid membrane [38], as well as Hecolin and Xiamen Innovax vaccines against hepatitis E [88], were developed and commercialized.…”
Section: Commercial Vaccines Based On Vlp and Prospects Of Broadeningmentioning
confidence: 99%
“…Because over 80% of all HPV associated cancers occur in the cervix, nearly all of the evidence for prophylactic vaccine prevention of incident type-specific HPV infection is in cervical disease (TORRE et al, 2015 Immunogenicity, indicated by antibody titre levels is the primary recognized endpoint in VLP based HPV vaccine studies and titres are dependent on the number of doses and timing (LEHTINEN et al 2012). Studies showed that seropositivity for anti-HPV16 titers after 5 years is high for both Cervarix and Gardasil (GODI et al, 2015) and Gardasil9 induces similar anti-HPV16/18 responses as Gardasil (GUEVARA et al, 2017).…”
Section: Hpv Vaccinesmentioning
confidence: 99%